ROLE OF WOMEN IN R. K. NARAYAN’S NOVELS - Harisha D L; Guptha, Arthi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
R.K. Narayan is the greatest Indian writers in English. He is essentially a writer of middle class characters of Malgudi, a place of his imagination in South India. He has given a wide gallery of both male and female characters in his writings. In each of his novel, there is at least one female character who occupies an important place in the story and Rosie is such a female character in The Guide. She represents a modern woman who is educated and ambitions and strives to attain independent economic entity according to her own taste and talent although she has to pay a heavy price for it. The other female characters in the novel are Raju’s mother and Velan’s sister. Raju’s mother represents the conservative and orthodox women who follow tradition and culture. She is a dutiful wife and a loving mother. She advises both Raju and Rosie about what is right and what is wrong. But when no heed is paid to her advice, she leaves her home and goes with her brother to live with him. Velan’s sister plays a very brief role but her role is important in making Raju appear as a saint in the novel. This paper is a humble attempt to study this aspect of R.K. Narayan’s characterization.